2021
DOI: 10.1016/j.scitotenv.2020.143161
|View full text |Cite
|
Sign up to set email alerts
|

How air quality and COVID-19 transmission change under different lockdown scenarios? A case from Dhaka city, Bangladesh

Abstract: The transmission of novel coronavirus (COVID-19) can be reduced by implementing a lockdown policy, which has also been proven as an effective control measure for air pollution in the urban cities. In this study, we applied ground- and satellite-based data of five criteria air pollutants (PM2.5, NO 2 , SO 2 , O 3 , and CO) and meteorological factors from March 8 to May 15, 2020 (before, partial-, and full-lockdown). The generalized additive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 58 publications
5
63
1
Order By: Relevance
“…The effect of air pollution on COVID-19 spread during early outbreaks was weaker than the effect of local climate. In the early stages of the global outbreak, we observed more severe outbreaks in regions with poor air quality, as gauged by their higher PM2.5 levels, in line with studies suggesting that poor air quality may enhance local transmission and may increase COVID-19 related mortality, possibly not independently of local meteorological conditions (Azuma et al, 2020; Bianconi et al, 2020; Rahman et al, 2020; Wu et al, 2020b; Yao et al, 2020; Zhang et al, 2020). Air pollution can influence COVID-19 spread through different pathways.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The effect of air pollution on COVID-19 spread during early outbreaks was weaker than the effect of local climate. In the early stages of the global outbreak, we observed more severe outbreaks in regions with poor air quality, as gauged by their higher PM2.5 levels, in line with studies suggesting that poor air quality may enhance local transmission and may increase COVID-19 related mortality, possibly not independently of local meteorological conditions (Azuma et al, 2020; Bianconi et al, 2020; Rahman et al, 2020; Wu et al, 2020b; Yao et al, 2020; Zhang et al, 2020). Air pollution can influence COVID-19 spread through different pathways.…”
Section: Discussionsupporting
confidence: 89%
“…The role of environmental drivers on COVID-19 spatial patterns and growth rate is controversial (Araújo et al, 2020; Carlson et al, 2020a; Carlson et al, 2020b; National Academies of Sciences Engineering and Medicine, 2020). Some authors suggested that this disease had a reduced impact and spread in warm climates, and in areas with low pollution and experiencing intense UV radiation (Merow and Urban, 2020; Rahman et al, 2020; Runkle et al, 2020; Sajadi et al, 2020; Sobral et al, 2020; Wu et al, 2020b; Wu et al, 2020c; Zhang et al, 2020), while others reported that socio-economic factors and airport connections have a much stronger impact than environmental drivers (Coelho et al, 2020; Jaffe et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strict measures related to COVID-19 had a large impact on economic activities, including energy production, industrial activities, and transportation [4,5]. As a result, the emissions of many atmospheric components were significantly reduced [6][7][8][9]. There was a 3.7% decrease in Chinese carbon dioxide (CO 2 ) emissions in the first half of 2020 related to the COVID-19 pandemic [10].…”
Section: Introductionmentioning
confidence: 99%
“…The lockdown not only decreased the air pollution significantly but also affected through social distancing and isolation of the COVID-19 cases from the unaffected population. A study informed that the lowest rate of COVID-19 confirmed cases were found in full lockdown ( Rahman et al, 2021 ). The COVID-19 lockdown certainly is expected to have a synergistic effect in bringing down transmission of virus.…”
Section: Overview Of Possible Transmission Pathwaysmentioning
confidence: 99%